2021
DOI: 10.1155/2021/5545178
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Diffusion Tensor Imaging for Infants’ Brain Development Retardation Caused by Pre-Eclampsia

Abstract: Objective. Pre-eclampsia (PE) can cause brain development delay in infants. This work aims to characterize the pattern differences of brain white matter development in premature infants under PE conditions and those without. Methods. Eighty preterm infants delivered by women with PE were selected as the PE group, and ninety-six preterm infants of the same period born to women without high-risk perinatal factors were used as control. All infants underwent diffusion tensor imaging (DTI) examination. The fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A brain imaging study using diffusion tensor imaging provided the first report of lower fractional anisotropy values from the splenium region in premature infants whose mothers had PE, thus indicating that PE might be a factor in a neurodevelopmental delay of the brain microstructure in the CC, especially in the splenium region. 24 It is unknown whether or to what extent the microstructural alterations occur in the CC of fetuses with FGR in pregnancies with PE or GH. Using diffusion MRI, we identified reduced ADC values in the anterior third region and the splenium region of the fetal CC in the PE or GH with FGR group when compared with the 2 control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A brain imaging study using diffusion tensor imaging provided the first report of lower fractional anisotropy values from the splenium region in premature infants whose mothers had PE, thus indicating that PE might be a factor in a neurodevelopmental delay of the brain microstructure in the CC, especially in the splenium region. 24 It is unknown whether or to what extent the microstructural alterations occur in the CC of fetuses with FGR in pregnancies with PE or GH. Using diffusion MRI, we identified reduced ADC values in the anterior third region and the splenium region of the fetal CC in the PE or GH with FGR group when compared with the 2 control groups.…”
Section: Discussionmentioning
confidence: 99%
“…12 Exposure of infants to PE has been associated with significant retardation in the microstructural development of the white matter in the splenium region. 24 There was evidence that perinatal composite outcomes were increasingly used to evaluate the neonatal prognosis. 13,26 In a multicenter prospective study of extremely preterm infants, adverse perinatal outcomes (including necrotizing enterocolitis, infection, and intracranial hemorrhage) were associated with a range of high-risk neurodevelopmental impairment assessed at the 2-year follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes an increased risk of neurodevelopmental disorders, particularly autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and intellectual disability (ID) ( Maher et al, 2018 ; Sun et al, 2020 ; Greca et al, 2021 ; Wang et al, 2021 ). In addition, recent neuroimaging studies have revealed alterations in brain structure, function and metabolites of children prenatally exposed to PE ( Rätsep et al, 2016 ; Figueiró-Filho et al, 2017 ; Mak et al, 2018 ; Katsuki et al, 2021 ; Xing et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This includes an increased risk of neurodevelopmental disorders, particularly autism spectrum disorder (ASD), ADHD, and intellectual disability (ID) [6][7][8][9]. In addition, recent neuroimaging studies have revealed alterations in brain structure, function and metabolites of children prenatally exposed to PE [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%